Sistem Informasi Bimbingan Akademik Mahasiswa Untuk Mengatasi Social Distancing Pada Masa Pandemi Covid-19 - Musta’inul Abdi (Jurnal Teknologi, 2021)
Since the COVID-19 pandemic was declared a global pandemic in mid-March 2019, all countries in the world are struggling to overcome this pandemic. This pandemic greatly affects all sectors of human activity such as social, economic, and education. The Indonesian government has given instructions on preventing the spread of the COVID-19 virus in the university environment, all educational activities must be carried out online. In this difficult situation, students, lecturers, and universities find it difficult to adapt to these new habits. the process of student guidance and counseling as a means of supporting students in their education and monitoring student development becomes problematic. So that a solution is needed to solve the problem, the student guidance and counseling information system is a solution that can be done. This system is able to overcome the problem of space and time constraints for students and lecturers to conduct consultations. The results of the survey testing that have been carried out, 90% of respondents agree that this system is feasible to implement and is able to overcome the problems of guidance and counseling during social distancing.